2018
DOI: 10.1111/jcmm.13518
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CCAT2 promoted osteosarcoma cell proliferation and invasion

Abstract: Long non‐coding RNA (lncRNA) plays important roles in tumour progression. Accumulating studies demonstrated that lncRNA colon cancer‐associated transcript 2 (CCAT2) acted as an oncogene in many tumours. However, the role of CCAT2 in the development of osteosarcoma has not been elucidated. In our study, we indicated that CCAT2 expression was up‐regulated in osteosarcoma tissues and cell lines (SOSP‐9607, MG‐63, U2OS and SAOS‐2). In addition, osteosarcoma cases with higher CCAT2 expression had a poorer disease‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 40 publications
(52 reference statements)
0
35
0
Order By: Relevance
“…In recent years, lncRNAs are reported to have important epigenetic regulatory roles in diverse biologic cellular processes. Studies have indicated that lncRNAs play important regulatory roles in tumorigenesis and metastasis [10,11]. Our study demonstrated that lncRNA HIF2PUT may play an anti-oncogene role in the development of osteosarcoma.…”
Section: Discussionmentioning
confidence: 52%
“…In recent years, lncRNAs are reported to have important epigenetic regulatory roles in diverse biologic cellular processes. Studies have indicated that lncRNAs play important regulatory roles in tumorigenesis and metastasis [10,11]. Our study demonstrated that lncRNA HIF2PUT may play an anti-oncogene role in the development of osteosarcoma.…”
Section: Discussionmentioning
confidence: 52%
“…17,18 FoxM1 plays various critical roles in the regulation of cell behavior, including differentiation, proliferation, and apoptosis. 17,18 FoxM1 plays various critical roles in the regulation of cell behavior, including differentiation, proliferation, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, long non-coding RNAs (lncRNAs), which exceed 200 nucleotides in length and do not encode proteins [18][19][20], participate in multiple biological processes, including cell proliferation and invasion [21,22]. They are key regulators of cancer progression and modulate the transcription of cancer-related genes through chromatin modification and transcriptional processes [23][24][25].…”
Section: Introductionmentioning
confidence: 99%